A transfiguração da palavra pela natureza na poesia de Manoel de Barros - MARTINS, Samita Vieira Barbosa (2019)
The matogrossense poet Manoel de Barros, who guides us throughout this research, brings in his poetry work a very close meaning of poetry to the Octavio Paz definition of it, as a powerful force which can join the opposites, bringing harmony to the desharmony we see in the world. It is possible to notice all along Manoel de Barros’s poetry the necessity to highlight what seems incompatible and unimportant, trying to show a big value about what is undermost. The games with the themes, mainly the theme about nature and envirolment, and with words in his poetry makes us think about what is beyond the meanings on it, guiding us to go farther on the reading of the poem and redefining the way we see the world around us, building a path that mixes the words with nature elements in a communion. And to the study here presented, we have selected the following poems on Manoel de Barros’s work to be better analysed: the poema number “XI” in the third part of the book Livro das ignorãças, the poem called “Palavras”, the one called “Borboletas”, and the poem “Línguas” presented on the book Ensaios fotográficos, “Poema”, in Tratado geral das grandezas do ínfimo, the poems “II”, “VI” and “35” of the book Menino do mato, and the poem “16”, in the first part of the book Retrato do artista quando coisa. They will guide us on investigation about how the poet works with the words on his poetry, making language different and renewed through changes he makes on the words he uses in the poems. To help this investigation about Manoel de Barros’s work with language and its relation with nature, we use teorical views that help us understand better how it can work, dialoguing with Mircea Eliade and his perspective of and archaic ontology, getting to know better the primordial aspects of Manoel de Barros’s poetry on (re)creation and putting this poetry closer to the primal. We have also Martin Heidegger’s work thinking about ontology in hemeneutics perspective, following the way the philosopher reads Hölderlin’s and Geog Trakl’s poetries, working with how is the language used on poetry. We aldo dialogue with Gaston Bachelard’d thoughts about the elements of nature to help us on reading how they are presented on Manoel de Barros’s poetry, mainly the air and the water, and how productive they are throughout his poetical project. And to end our study we talk again about the influence of the primitive way to think about the world in his poetry presented on the bringing of indigenous views, dialoguing in this section with Eduardo Viveiros de Castro and his studies about perspectivism.